Integrating Evolutionary and Functional Tests of Adaptive Hypotheses: A Case Study of Altitudinal Differentiation in Hemoglobin Function in an Andean Sparrow, Zonotrichia capensis - Cheviron, Zachary A.; Natarajan, Chandrasekhar; Projecto-Garcia, Joana; Eddy, Douglas K.; Jones, Jennifer; Carling, Matthew D.; Witt, Christopher C.; Moriyama, Hideaki; Weber, Roy E.; Fago, Angela; Storz, Jay F. (Molecular biology and evolution, 2014)
In air-breathing vertebrates, the physiologically optimal blood-O2 affinity is jointly determined by the prevailing partial pressure of atmospheric O2, the efficacy of pulmonary O2 transfer, and internal metabolic demands. Consequently, genetic variation in the oxygenation properties of hemoglobin (Hb) may be subject to spatially varying selection in species with broad elevational distributions. Here we report the results of a combined functional and evolutionary analysis of Hb polymorphism in the rufous-collared sparrow (Zonotrichia capensis), a species that is continuously distributed across a steep elevational gradient on the Pacific slope of the Peruvian Andes. We integrated a population genomic analysis that included all postnatally expressed Hb genes with functional studies of naturally occurring Hb variants, as well as recombinant Hb (rHb) mutants that were engineered through site-directed mutagenesis. We identified three clinally varying amino acid polymorphisms: Two in the αA-globin gene, which encodes the α-chain subunits of the major HbA isoform, and one in the αD-globin gene, which encodes the α-chain subunits of the minor HbD isoform. We then constructed and experimentally tested single- and double-mutant rHbs representing each of the alternative αA-globin genotypes that predominate at different elevations. Although the locus-specific patterns of altitudinal differentiation suggested a history of spatially varying selection acting on Hb polymorphism, the experimental tests demonstrated that the observed amino acid mutations have no discernible effect on respiratory properties of the HbA or HbD isoforms. These results highlight the importance of experimentally validating the hypothesized effects of genetic changes in protein function to avoid the pitfalls of adaptive storytelling.